Elizabeth Durack interviewed by Helene Charlesworth for the Battye Library collection - Durack, Elizabeth, 1915-2000.; Charlesworth, Helene Barr.; State Library of Western Australia; J.S. Battye Library of West Australian History (1997)
Elizabeth Durack, artist and illustrator, talks about the Durack family and their stations in the Kimberley region of Western Australia; her family background; childhood and education. She then discusses the Eddie Burrup paintings, her reasons for producing them and the central theme of this art. Durack also talks about her art and her future projects.
The J.S. Battye Library of West Australian History is part of the State Library of Western Australia.
Interview conducted in association with the J.S.Battye Library of West Australian History.
Recorded between Nov. 21, 1997 and June 8, 1998 in Dalkeith, W.A.
Also available online
Timed summary (10 p.) and corrected transcript available (typescript, 59 leaves).
Keywords: Durack, Elizabeth, -- 1915-2000 -- Interviews; Women painters -- Australia -- Interviews; Artists